Experimental research in expatriation and its challenges: A literature review and recommendations. (May 2020) - Noethen, Daniela; Alcazar, Rocio
Via a systematic literature review, this article draws attention to the alarming scarcity of experimental studies and the ensuing shortness of evidence for causality in the field of expatriate management. Only 17 articles could be identified, published over more than 20 years, which utilize randomized experiments or quasi-experiments on topics of expatriation. Moreover, these articles show specific patterns, such as dealing exclusively with pre-departure and on-assignment issues, or, in their majority, sampling individuals who interact with expatriates rather than expatriates themselves. This lack of experimental studies is problematic, as it is difficult to establish causality between different variables without conducting experimental studies. Yet many critical issues in expatriation are precisely questions of causality. Hence, in this article, we provide resources to help move the expatriation field toward a more balanced use of different research methodologies and, thus, a greater understanding of the many relationships uncovered in past research. First, we identify four main challenges unique to conducting experimental research in the context of expatriation: Challenging data access, global sample dispersion, restricted manipulability of variables, and cultural boundedness of constructs and interpretations. Second, we provide strategies to overcome these challenges, based on studies included in the review as well as taking ideas from neighboring fields such as cross-cultural psychology. The article concludes with a discussion of how experimental research can take the field of expatriation forward and improve the decision-making process of practitioners managing international assignees.